2013
DOI: 10.1115/1.4023584
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Phonon Transport: From Interfaces to Nanostructures

Abstract: A wide range of modern technological devices utilize materials structured at the nanoscale to improve performance. The efficiencies of many of these devices depend on their thermal transport properties; whether a high or low conductivity is desirable, control over thermal transport is crucial to the continued development of device performance. Here we review recent experimental, computational, and theoretical studies that have highlighted potential methods for controlling phonon-mediated heat transfer. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 77 publications
3
34
0
Order By: Relevance
“…The reduction in thermal conductivity for the TiO 2 -based SL is in line with the results reported for the (ZnO) x /HQ SLs. This reduction in the thermal conductivity due to the periodic monolayers is consistent with the decrease in thermal conductivity with increased interface density in inorganic SLs [45,46].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The reduction in thermal conductivity for the TiO 2 -based SL is in line with the results reported for the (ZnO) x /HQ SLs. This reduction in the thermal conductivity due to the periodic monolayers is consistent with the decrease in thermal conductivity with increased interface density in inorganic SLs [45,46].…”
Section: Resultssupporting
confidence: 77%
“…As pointed out in purely inorganic SLs, the monotonic decrease in thermal conductivity due to increased interface density (and linearly increasing thermal resistance with increasing interface density) is due to incoherent scattering, where the phonons behave as particles and lose their phase information by scattering at the internal boundaries [45,46].…”
Section: Resultsmentioning
confidence: 80%
“…In many literatures, it has been confirmed that the interface in the composites play a significant role in their thermal conductivity [236][237][238][239][240][241]. Heat transfer at the interface of two different materials mostly happens with a temperature discontinuity [242].…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…This phenomenon was observed first at the interface of a metal and liquid helium [243], while later it has been found at the interface of two solids [244]. The heat loss at the interface of two different materials is due to the phonon scattering at this region [236,238,239]. Phonon scattering can be significantly impacted by dimensions of fillers, the matrix, and their interfacial regions.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation